2014
DOI: 10.5194/nhess-14-2179-2014
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of the Weather Research and Forecasting (WRF) model for simulating typhoons

Abstract: Abstract. The Weather Research and Forecasting (WRF) model includes various configuration options related to physics parameters, which can affect the performance of the model. In this study, numerical experiments were conducted to determine the best combination of physics parameterization schemes for the simulation of sea surface temperatures, latent heat flux, sensible heat flux, precipitation rate, and wind speed that characterized typhoons. Through these experiments, several physics parameterization options… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…It employs an Eulerian mass-coordinate solver with a non-hydrostatic approach, and a terrain following Eta-coordinate system in the vertical. It is a state-of-the-art mesoscale model used in a variety of studies (Clifford et al, 2011;T. Haghroosta et al, 2014;J.…”
Section: Methodology 221 Model Descriptionmentioning
confidence: 99%
“…It employs an Eulerian mass-coordinate solver with a non-hydrostatic approach, and a terrain following Eta-coordinate system in the vertical. It is a state-of-the-art mesoscale model used in a variety of studies (Clifford et al, 2011;T. Haghroosta et al, 2014;J.…”
Section: Methodology 221 Model Descriptionmentioning
confidence: 99%
“…Tornadoes occur in many parts of the world (Fujita, 1973). Several publications during the last several decades have presented historical records concerning tornadic activity (e.g., Meaden, 1976;Tooming and Peterson, 1995;Peterson, 1998;Reynolds, 1999;Tyrrell, 2003;Macrinoniene, 2003;Dotzek, 2003;Nastos and Matsangouras, 2010;Gayà et al, 2000;Brázdil et al, 2012;Rauhala et al, 2012;Haghroosta et al, 2014). As far as tornadic activity over Greece is concerned, a comprehensive spatial distribution of a total of 612 events (171 tornadoes, 374 waterspouts and 67 funnel clouds) recorded in 405 d was presented (Matsangouras et al, 2014a, b: Nastos and as there were several days with multiplied events within the period 1709-2012 (Fig.…”
Section: Tornadoes and Waterspoutsmentioning
confidence: 99%
“…A number of researchers have noted the importance of convection and especially mesoscale convective systems in producing warm season precipitation. Heideman and Fritsch (1984) estimated that about half of warm season precipitation over the United States is produced directly by mesoscale systems or phenomena. In long lasting, circular shaped, convective systems, using satellite imagery found that such systems accounted for approximately 30 % to 70 % of warm season precipitation between the Rocky Mountains and Mississippi River.…”
Section: Heavy Convective Precipitationmentioning
confidence: 99%
“…Tornadoes occur in many parts of the world (Fujita, 1973). Several publications during the last several decades have presented historical records concerning tornadic activity (e.g., Meaden, 1976;Tomming et al, 1995;Peterson, 1998;Reynolds, 1999;Tyrrel, 2003;Macrinoniene, 2003;Dotzek, 2003;Nastos and Matsangouras, 2010;Gayà et al, 2000;Brázdil et al, 2012;Rahuala et al, 2012;Haghroosta, et al, 2014). As far as tornadic activity over Greece is concerned, a comprehensive spatial distribution of a total of 612 events (171 tornadoes, 374 waterspouts and 67 funnel clouds), recorded on 405 days was presented (Matsangouras et al, 2014a;, as there were several days with multiplied events, within the period 1709-2012 ( Figure 5).…”
Section: Tornadoes and Waterspoutsmentioning
confidence: 99%